Intermodal Transportation of Dangerous Goods - Andrea Galierikova; Jarmila Sosedova (Communications - Scientific letters of the University of Zilina, 2017)
The paper deals with intermodal transportation, broadly defined as a chain consisting of several transportation modes that are coordinated and interact in intermodal terminals to ensure door-to-door service. The goal of the article is to describe the road-sea intermodal flow, to define the responsibilities of each party of a transportation chain and to identify important issues and bottlenecks in the whole intermodal transportation. Recently, the demand for the transportation of dangerous goods has been rising. Transport of dangerous goods can have serious effects on the environment if an accident happens. The legal environment for each transport department, harmonisation of the rules and regulations for intermodal transportation and setting the responsibilities for every party of the transportation chain (such as forwarder, hauler, shipper and consignor) make the transports of dangerous goods more safe and efficient and can reduce risks and threats.